Archives information publishing new design in post-custodial regime: the national archives experience digital vaults - Jorente, Maria José Vicentini [UNESP] (Ios Press, 2012)
The uses of Information and Communication Technologies (ICT) and Web environments for creation, treatment and availability of information have supported the emergence of new social-cultural patterns represented by convergences in textual, image and audio languages. This paper describes and analyzes the National Archives Experience Digital Vaults as a digital publishing web environment and as a cultural heritage. It is a complex system - synthesizer of information design options at information setting, provides new aesthetic aspects, but specially enlarges the cognition of the subjects who interact with the environment. It also enlarges the institutional spaces that guard the collective memory beyond its role of keeping the physical patrimony collected there. Digital Vaults lies as a mix of guide and interactive catalogue to be dealt in a ludic way. The publishing design of the information held on the Archives is meant to facilitate access to knowledge. The documents are organized in a dynamic and not chronological way. They are not divided in fonds or distinct categories, but in controlled interaction of documents previously indexed and linked by the software. The software creates information design and view of documental content that can be considered a new paradigm in Information Science and are part of post-custodial regime, independent from physical spaces and institutions. Information professionals must be prepared to understand and work with the paradigmatic changes described and represented by the new hybrid digital environments; hence the importance of this paper. Cyberspace interactivity between user and the content provided by the environment design provide cooperation, collaboration and sharing knowledge actions, all features of networks, transforming culture globally.
Keywords: Web Publishing; Historical Archives; Information and Comunication Technologies; Post-custodial; Hypertext